"I will walk among you": the rhetorical function of allusion to Genesis 1-3 in the book of Leviticus - Harper, G. Geoffrey (Bulletin for Biblical research supplement, 2018)
"A methodologically constrained examination of the lexical, syntactical, and conceptual correspondence between the opening chapters of Genesis and Leviticus 11, 16, and 26. Explores the potential rhetorical function of allusion for the texts' original audience"--Provided by publisher